on, to European Union Policy on Artificial Intelligence Related to Cyber Crime - Maheswara Perbawa Sukawati (Hang Tuah Law Journal, 2020)
Artificial Intelligence is one of the sector in Revolution Industry 4.0 that become serious topic to discuss in every country in the world including the European Union itself. They believe that Artificial Intelligence can make the good benefit for the society, however the using of Artificial Intelligence usually make a negative impact for the society therefore the European Union made some Policy about the Artificial Intelligence to support about the Revolution Industry 4.0. The Policy about Artificial Intelligence have the purpose to regulate about using Artificial Intelligence in European Union basically for the members, everything about Artificial Intelligence have the relation with the Technology that have been develop nevertheless everything about technology, internet, computer, and data have already regulated in Convention on Cyber Crime Budapest 2001 therefore everything about Artificial Intelligence including the Policy of Artificial Intelligence in European Union have to related with the Convention on Cyber Crime.